2014
DOI: 10.1007/s00005-014-0303-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel Transgenic Rice-Based Vaccines

Abstract: Oral vaccination can induce both systemic and mucosal antigen-specific immune responses. To control rampant mucosal infectious diseases, the development of new effective oral vaccines is needed. Plant-based vaccines are new candidates for oral vaccines, and have some advantages over the traditional vaccines in cost, safety, and scalability. Rice seeds are attractive for vaccine production because of their stability and resistance to digestion in the stomach. The efficacy of some rice-based vaccines for infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 128 publications
(119 reference statements)
0
21
0
Order By: Relevance
“…Once within the gastrointestinal tract, the cell wall is then broken down by microbes and the intracellular material is released [112]. These crops are staple foods in target vaccination areas, are inexpensive to produce and easy to grow in large quantities [114,115]. These transgenic cells may then be able to deliver antigenic material to the intestines, where it is free to interact with the gut-associated lymphoid tissue.…”
Section: Plant-like Materialsmentioning
confidence: 99%
“…Once within the gastrointestinal tract, the cell wall is then broken down by microbes and the intracellular material is released [112]. These crops are staple foods in target vaccination areas, are inexpensive to produce and easy to grow in large quantities [114,115]. These transgenic cells may then be able to deliver antigenic material to the intestines, where it is free to interact with the gut-associated lymphoid tissue.…”
Section: Plant-like Materialsmentioning
confidence: 99%
“…Plant-based oral vaccines have advantages over the traditional vaccines in cost, safety, and scalability. Since 1990, researchers have manufactured edible plant-based vaccines in carrot, soybean, tomato, rice, potato, and tobacco against microbial pathogen antigens such as the heat-labile toxin B subunit (LTB) of enterotoxigenic Escherichia coli, cholera toxin B subunit (CTB), and antigens from Yersinia pestis and viruses, such as hepatitis B virus, rotavirus, and Norwalk virus [159]. Many conventional vaccines are not widely distributed in developing countries where those vaccines are urgently needed, because of high production costs and the requirement of better infrastructure.…”
Section: Oral Delivery Of Vaccines Using Food Materialsmentioning
confidence: 99%
“…These results show that the MucoRice vaccine could be stockpiled longer at room temperature and could be widely used for oral vaccination without cold-chain management. Rice-based oral vaccine developments are under way against many infectious diseases and noninfectious diseases such as allergy, autoimmunity, and Alzheimer's disease [159].…”
Section: Oral Delivery Of Vaccines Using Food Materialsmentioning
confidence: 99%
“…One of the first was a vaccine candidate based on the heat-labile enterotoxin B (LTB) subunit of enterotoxigenic Escherichia coli (ETEC) produced in transgenic potato, which protected against an ETEC challenge in animal studies and was also immunogenic in humans during a phase I clinical trial (Haq et al, 1995;Mason et al, 1998;Tacket et al, 1998); the same was shown when it was produced in transgenic corn (Tacket, 2007;Tacket et al, 2004). Many examples for Alzheimer's disease, allergic diseases, or autoimmune and infectious diseases show that rice is one of the preferred EPTs for therapeutic protein production (Azegami et al, 2015;Takaiwa et al, 2015). A first example is the MucoRice-CTB, an oral vaccine against cholera, which consists of the antigen of the cholera toxin B (CTB) accumulating in rice seed storage organelles.…”
Section: Edible Plant Tissues As a Platform For Production Of Mucosalmentioning
confidence: 99%
“…Edible plant tissues with GRAS status (such as fruits, seeds and certain leaves) can therefore be utilized as reservoirs of antibodies such as SIgAs for easy longtime storage and enabling quick availability after minimal processing when required for OPI. In the case of seeds, due to their low water content, they can be stored for years without losing antibody efficacy (Azegami et al, 2015;Virdi et al, 2013). If using more watery tissues, such as fleshy fruits and leaves, a step of lyophilization or spray-drying should be included prior to storing (Juarez et al, 2012;Su et al, 2015b).…”
Section: Final Remarksmentioning
confidence: 99%